Proof: Get New State 19

Let's prove the following theorem:

if expression state at time 19 = "return", then expression state at time 20 = "iterate_args"

Proof:

View as a tree | View dependent proofs | Try proving it

Given
1 expression state at time 19 = "return"
Proof Table
# Claim Reason
1 expression state at time (19 + 1) = "iterate_args" if expression state at time 19 = "return", then expression state at time (19 + 1) = "iterate_args"
2 19 + 1 = 20 19 + 1 = 20
3 expression state at time (19 + 1) = expression state at time 20 if 19 + 1 = 20, then expression state at time (19 + 1) = expression state at time 20
4 expression state at time 20 = "iterate_args" if expression state at time (19 + 1) = expression state at time 20 and expression state at time (19 + 1) = "iterate_args", then expression state at time 20 = "iterate_args"

Comments

Please log in to add comments